Estimation of Energy-Saving Potential Using Commercial SiC Power Converters - Lucas Barroso Spejo; Tanya Thekemuriyil; Renato Amaral Minamisawa (Energies, 2024)
This study evaluates the annual global energy-savings potential of various power electronics applications utilizing commercial silicon carbide (SiC) wide bandgap (WBG)-based power converters. As the first analysis to focus on real market products, our findings reveal that SiC-based converters offer significant energy-saving potential across all examined applications. Additionally, given the substantial yearly growth in installing photovoltaic (PV) systems and electric vehicle (EV) chargers, we project a considerable future energy-saving potential. This research underscores the importance of SiC technology in enhancing energy efficiency and supports its broader adoption in power electronics to achieve global energy savings.